SACCHAROMYCES CEREVISIAE-INDUCED APOPTOSIS OF MONOLAYER CERVICAL CANCER CELLS - Rajan, Teena; V, Benluvankar; S, Vincent (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The present study was undertaken to examine the effect of phagocytosis of killed yeast on the induction of apoptosis in monolayer of HeLa cells. Methods: HeLa cell line was incubated with different doses (1000-7.8 Î¼g/ml) of heat-killed Saccharomyces cerevisiae for 24, 48, and 72 hrs. The cytotoxicity against HeLa cell line during different exposure hours was screened by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-tetrazolium bromide assay. Induction of apoptosis was further confirmed by morphological and biochemical examination. Antiproliferative effect of yeast was examined under inverted microscope. Cell morphological changes were analyzed by fluorescent staining with propidium iodide. Results: The results showed that yeast induces cytotoxicity against HeLa cells in concentrations and during prolonged exposure periods. The viability of HeLa cells decreased from 85% to 45% during 72 hrs of treatment with 1000 Î¼g/ml of yeast cells. The inhibitory concentration 50% of heat-killed yeast required to induce 50% inhibition of HeLa cells was 62.5 Î¼g/ml. Apoptotic cells showed signs such as cell enlargement, membrane blebbing, and chromatin condensation. Furthermore, cell cycle analysis showed that S. cerevisiae treated HeLa cells and showed a typical apoptosis pattern of DNA content that reflected sub-G0 phase (corresponding to apoptotic cells). Conclusion: Results from the present work show that the heat-killed yeast has anticancer activity and it includes apoptosis of HeLa cells in vitro.